Safety and Efficacy of Apixaban Use in Peritoneal Dialysis: A Review of the Literature. (June 2021) - Amani, Armaghan; Fellers, Caitlin M.; Eyebe, Antoinette; Hall, Alyssa; Howard, Meredith L.
Objective: To review the safety and efficacy of apixaban for the treatment of nonvalvular atrial fibrillation or venous thromboembolism in patients receiving peritoneal dialysis (PD).Data Sources: A PubMed and MEDLINE search was conducted through December 2020 using the following keywords and Medical Subject Headings (MeSH) terms alone or in various combinations: apixaban, peritoneal dialysis, continuous ambulatory peritoneal dialysis, end-stage renal disease, and hemodialysis.Study Selection and Data Extraction : English-language studies evaluating clinical outcomes pertaining to the use of apixaban in end stage renal disease (ESRD), which included patients receiving peritoneal dialysis were eligible for inclusion.Data Synthesis: Four studies were identified that met inclusion for this review, all retrospective in nature. These studies compared the safety and efficacy of apixaban with standard therapy in ESRD included patients on dialysis, with a very limited number of subjects receiving PD. In these studies, apixaban was shown to be potentially safer and more effective than warfarin. Outcomes did not differentiate between patients receiving PD or not.Conclusions: Use of apixaban in patients receiving PD may be safe and effective based on data from limited patients. Pharmacokinetics and pharmacodynamics of apixaban in the PD setting is an important question that clinicians should consider with use of this medication in the ESRD population. More studies focusing on the PD population are needed to better assess the use of apixaban in this understudied population.